The Effects of Invented Spelling Instruction on Literacy Achievement and Writing Motivation - Katie Schrodt; Erin FitzPatrick; Sungyoon Lee; Debra McKeown; Alexis McColloch; Kimberly Evert (MDPI AG, 2024)
Early writing performance strongly predicts long-term literacy performance. It follows that early underachievement in writing is highly correlated with early underachievement in reading. One strategy teachers and students can use to approach writing in the kindergarten classroom is invented spelling. Invented spelling is children's spontaneous or self-directed attempts to represent words in print by matching sounds to known letters or phonics patterns. A quasi-experimental study was used to evaluate the impact of invented spelling on foundational literacy skills and writing motivation in 63 kindergarten students at a rural school in the Mid-South. The research questions focused on the impact of invented spelling instruction on a variety of literacy outcomes, including foundational skills, spelling, and motivation. The results indicate the significant main effects of invented spelling instruction on students' invented spelling (p < 0.001), conventional spelling (p < 0.001), complex vocabulary use (p < 0.001, writing motivation (p = 0.040), and writing achievement (p < 0.001). Other outcomes as well as implications and future directions are reported. The invented spelling intervention encouraged low-stake risk taking when writing and removed barriers to writing entry. Allowing time and space for invented spellings means students can focus on communicating their ideas in print without being hindered by the expectation to conform to conventional spellings.